PEMANFAATAN RUMAH BERSEJARAH INGGIT GARNASIH SEBAGAI UPAYA DALAM MENINGKATKAN LITERASI SEJARAH - Samudra Eka Cipta; Wawan Darmawan (Jurnal Pendidikan Nusantara, 2022)
This research seeks to explain the use of Inggit Garnasih's historic house in Astana Anyar, Bandung City, to improve historical literacy skills. Inggit Garnasih's historic house contains local and national elements in Indonesian historiography (historical writing). This research indeed uses a participatory approach and uses a descriptive-analytical system. This research is expected to introduce one of the historical tourist destinations in the city of Bandung.